2008
DOI: 10.1021/ja804628x
|View full text |Cite
|
Sign up to set email alerts
|

Base-by-Base Dynamics in DNA Hybridization Probed by Fluorescence Correlation Spectroscopy

Abstract: Thermodynamics and dynamics of DNA hybridization/dehybridization at a terminal of a DNA duplex are investigated using steady-state fluorescence and fluorescence correlation spectroscopy (FCS). We introduce two pairs of dyes with different characteristic distances in fluorescence resonance energy transfer (FRET) to investigate the same process. The phenomenal discrepancy in the experimental observations between our two FRET pairs is incompatible with the traditional two-state model. We propose a so-called stret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 37 publications
(116 reference statements)
2
61
0
Order By: Relevance
“…Previous studies on dynamics of dsDNA bubbling (22), zippingunzipping (23), and DNA hairpin folding (30) imply that the relaxation time of spontaneous single-base flipping should be on the order of 10 ms. Although the conventional FCS (31) and singlemolecule imaging based on total internal reflection fluorescence microscopy (TIRFM) (32) are powerful tools for dynamic studies under equilibrium, their time windows are not suitable for relaxations around 10 ms.…”
Section: Significancementioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies on dynamics of dsDNA bubbling (22), zippingunzipping (23), and DNA hairpin folding (30) imply that the relaxation time of spontaneous single-base flipping should be on the order of 10 ms. Although the conventional FCS (31) and singlemolecule imaging based on total internal reflection fluorescence microscopy (TIRFM) (32) are powerful tools for dynamic studies under equilibrium, their time windows are not suitable for relaxations around 10 ms.…”
Section: Significancementioning
confidence: 97%
“…In other words, the fluctuation probed by the NMR studies should be reassigned to base wobbling instead of flipping. Another well-known relaxation method, fluorescence correlation spectroscopy (FCS) coupled with fluorescence resonance energy transfer (FRET), has been applied to investigate many DNA conformational dynamics [e.g., DNA bubble breathing (22) and base zipping-unzipping (23)]. However, FRET measurement is sensitive to distance roughly from 2 to 7 nm, whereas the single-base flipping takes place at a distance shorter than 2 nm.…”
mentioning
confidence: 99%
“…Using a FRET nucleic acid probe, the dynamics of nucleic acid itself, including hybridization/dehybridization and self-assembly, can be studied. [94][95][96][97] Majima and co-workers used a dual-labeled DNA probe to investigate the detailed conformational dynamics of i-motif shapes. 94 A donor and an acceptor are labeled at the terminal of the cytosine (C)-rich ssDNA to monitor the change of diffusion rates under different pH conditions.…”
Section: Fluorescence Correlation Spectroscopy-based Biosensingmentioning
confidence: 99%
“…They found that hybridization rate constants were determined by different temperatures and salt concentrations. Chen et al 27 and Chen et al 28 analyzed the origin of the specific recognition of structured DNA and investigated base thermodynamics and dynamics of DNA hybridization/ dehybridization at a terminal of a DNA duplex. They proposed that the intermediate states are existent in hairpin folding and unfolding and that the hairpin opens in a concerted manner during the hybridization.…”
Section: Introductionmentioning
confidence: 99%
“…It implies that, in order to form the duplex, the hairpin-stem-loop should be unjointed in hybridization processes and respective melting temperatures should be comparable for all reactions that were taking place, because the hybridization temperature can impact the stability of double-stranded DNA. 27,29,30 In the previous one-step hybridization experiment, we have designed shorter single-stranded probe and target molecules and increasing the incubation temperature. Nevertheless, the result showed that reducing strand length could weaken detection selectivity and increasing temperature could degrade biosensor performance.…”
Section: Introductionmentioning
confidence: 99%